Improvement of halitosis by probiotic bacterium Weissella cibaria CMU: A randomized controlled trial - Han, Hee-seung; Yum, Haeji; Cho, Young-Dan; Kim, Sungtae (Frontiers in Microbiology, 2023)
Several in vitro and in vivo studies have evaluated the effect of probiotics on oral health; however, human clinical studies are still limited. Therefore, this study aimed to examine the effects of Weissella cibaria Chonnam Medical University(CMU)-containing tablets on halitosis. This randomized, double-blinded, placebo-controlled study included 100 adults with halitosis (age, 20–70 years). The participants were randomly assigned to the test group (n=50) and control group (n=50). One tablet [1×108 colony forming units (CFU)/tablet] was to be taken each day over 8 weeks. The concentrations of volatile sulfur compounds (VSCs), bad breath improvement scores, and oral colonization of W. cibaria were measured. Psychosocial indicators including depression, self-esteem, oral health-related quality of life, and subjective oral health status were evaluated. Most variables were assessed at baseline, 4, and 8 weeks, and W. cibaria number and safety variables were assessed at baseline and 8 weeks. Intergroup comparisons were carried out using Student's t-test, Chi-square test, or Fisher's exact test on per-protocol analysis. Intragroup differences before and after intake were analyzed using the linear mixed-effect model (LMM). Per-protocol analysis was carried out in the test group (n=45) and control group (n=46). Total VSC was significantly lower in the probiotics group than in the placebo group at baseline (week 0, p = 0.046) and at 8 weeks (p = 0.017). The sum of hydrogen sulfide and methyl mercaptan did not differ significantly between the groups at baseline; however, it was significantly lower in the probiotics group than in the placebo group at week 8 (p = 0.012). Bad breath improvement (BBI) scores were significantly reduced at week 8 (p = 0.006) in the probiotics group. Statistically significant intergroup differences were observed for changes in the level of W. cibaria at week 8 (p < 0.001). Psychological indicators significantly improved from baseline to week 8 in the probiotics group. No safety issues were observed in either group. The levels of W. cibaria was higher in patients with halitosis using W. cibaria CMU-containing tablets. The subjective degree of bad breath and psychological indicators were improved in patients with halitosis using W. cibaria CMU-containing tablets.